The Role of Depression in Existential Dread: A Psychological and Existential Perspective on the COVID-19 Pandemic - M Razkiazka MH (Jurnal Cakrawala Akademika, 2024)
The COVID-19 pandemic has led to significant mental health challenges, notably depression, which has emerged as a typical psychological response to existential crises triggered by the pandemic. This paper examines the psychological underpinnings of depression during existential crises, drawing on the theories of Ernest Becker about when individuals are confronted with uncertainty and mortality. Freud’s theory of transference explains the tendency to project one’s anxieties onto external figures, such as authority or religious entities, during times of crisis. Although existential dread plays a role, the focus is on how the inability to find meaning during crises leads to depression. Philosophers like Sartre and Kierkegaard provide further insights into human freedom and the search for meaning. Still, the psychological responses—especially depression—remain central to understanding the emotional toll of the pandemic. The paper concludes that social and spiritual support systems are crucial for addressing depression, urging individuals to seek help through both psychological and spiritual means.